2019
DOI: 10.1016/j.biortech.2019.121485
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis kinetics of biomass wastes using isoconversional methods and the distributed activation energy model

Abstract: In this work, a thermogravimetric analyser was used to assess the pyrolysis kinetics of pineapple, orange and mango peel wastes and agro-industrial by-products, rice husk and pine wood. Five isoconversional methods (KAS, FWO, Starink, Vyazovkin and Friedman) and one model-fitting method (DAEM) accurately fitted the experimental data at three heating rates (5, 10 and 20°C/min) between 10% and 90% conversion.These methods agree with the trends shown by the activation energy (E a ) distribution calculated, with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(52 citation statements)
references
References 44 publications
5
47
0
Order By: Relevance
“…The wooden chips and the wheat straw have E a of 85 kJ•mol −1 and 70 kJ•mol −1 , respectively [29]. The relations between the type of biomass and decomposition kinetics were also observed in other studies; the E a was from 150 to 550 kJ•mol −1 depending on the type of biomass [30,31]. It should be noted that the heating rate (β) also has an important impact on the kinetics.…”
Section: Introductionsupporting
confidence: 67%
“…The wooden chips and the wheat straw have E a of 85 kJ•mol −1 and 70 kJ•mol −1 , respectively [29]. The relations between the type of biomass and decomposition kinetics were also observed in other studies; the E a was from 150 to 550 kJ•mol −1 depending on the type of biomass [30,31]. It should be noted that the heating rate (β) also has an important impact on the kinetics.…”
Section: Introductionsupporting
confidence: 67%
“…Friedman approach had higher percentage than 16 % (KAS) or 4% (FWO). Also, it is clear that the maximum Ea was achieved at the progressing conversion rate within the range of 0.3–0.7, while the lowest Ea was at low conversion rates in the ranges of 0.1−02 and higher conversion rate (0.9) because of simultaneously generated reactions and simultaneous contacting of unstable radicals [ 60 , 61 ]. This means that thermal decomposition of face masks using pyrolysis process is a complex process and needs a multi-stage reaction mechanism for different components such as lignin, cellulose, hemicelluloses, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Parameters were calculated using different relations from literature such as Coast and Redfern, Agrawall and Sivasubramanian methods in order to compare the values obtained [24]. Meanwhile, Garrido et al [41] studied the thermal decomposition of viscoelastic memory foam by TG Analysis under different atmospheres and proposed a model with three consecutive reactions and the kinetic parameters using integral methods that involve all the heating rates evaluated, which gives more accurate parameters [49,50]. The above agree with Anca-Couce et al [51], who compared kinetic parameters obtained by model free methods and model fitting methods during beechwood pyrolysis and concluded that model fitting methods are more reliable and show a better fit.…”
Section: Introductionmentioning
confidence: 99%